Sliding Window Algorithm for Evaluation of Medical Symbols - Shamsutdinovich, Ikromov Shakhobiddin; Adkhamjanovich, Akbarov Chingiz; Primovich, Juraev Gulomjon (International Journal on Integrated Education, 2022)
This article discusses about sliding window algorithm for evaluation of medical symbols and given some important information.